Metafilozoficzne aspekty współczesnej myśli kosmologicznej - Leciejewski, Sławomir (Człowiek i Społeczeństwo, 2022)
The objective of this article is to provide an answer to the question as to how to philosophize within the context of science, which constitutes a more specific version of one of the essential metaphilosophical questions: how should one philosophize? A compelling answer to such inquiries was proposed at the end of the 20th century by the Cracow philosophers of nature and went under the name of „philosophy in science” research program. In this elaboration, on the basis of findings originating in the cosmological domain, I analyze to what extent this is indeed an innovative answer to the metaphilosophical question stated above – that is how to philosophize within the context of science.